Factors in achieving technology transfer project success : a case study of third party claims administration in Malaysia - Lim, Chin Kuan (2016)
Technology transfer is a complicated process that assisting the claim administration to deal with the complexity and efficiency of projects as well as the increasing demands and satisfaction of clients. Many developed countries that had raised their fund for technology transfer investment, it resulted that the productivity has increased within their claim administration. However, Malaysia is a slow adopting technology transfer compare to the other countries. Therefore, this research is to study how the technology transfer process in the claim administration industry and whether it can help in achieving project success. It’s also evaluating the factors of technology transfer process to see what the factors that will influence technology transfer implementation. A third party administration company in Malaysia was chosen to be a case for study. There are totally eight interviewees had been selected from the top level management of the Third Party Claims Administration company. The research shows that the factors affecting the technology transfer implementation include individual, organizational, and technological level factors. The results also show that the technology transfer process can assist in achieving technology project success by meeting the project criteria which are the cost, scope, time, quality, and the customer satisfaction. The possibility of the project success will increase if the technology transfer implementation practices are effective. This study can provide the baseline information for the technology transfer process for third party administrative company.